KOMPOSISI DAN KEANEKARAGAMAN JENIS IKAN KARANG DI PERAIRAN TELUK PALU - Putra, Aswad Eka; Akbar, Mohammad (AgriSains, 2017)
Reef fish resources in Palu Bay are under exploitation pressure with increasing demand of fish for human consumption. This study is aimed to analyze the reef fishes composition dan biodiversity in Palu Bay. Field survey was conducted in Palu Bay, Central Sulawesi, in June-July 2017. This research used a survey method on data collection of reef fishes in the form of visual census methods (UVS) and methods of UPT (Underwater Photo Transect). Three sampling station were chosen to represent reef fishes condition in Palu Bay. Results of research in Palu Bay, the reef fish composition dominated by major fishes (54%), then target fishes (40%) and indicator fishes (6%). The reef fish biodiversity index has an average of 2.44 with a range from 2.19 to 2.66, means that biodiversity is in moderate category.Keyword: Biodiversity, Reef Fishes, Palu Bay